Pengaruh Metode Pembelajaran Berbasis Kisah Islami terhadap Peningkatan Motivasi Belajar dan Pemahaman Konsep Agama Peserta Didik - Rahma Zulfa Tsania (Lembaga Pengkajian Pengembangan Pendidikan dan Kewirausahaan, 2025)
This study aims to deeply understand the influence of Islamic story-based learning methods on increasing students' learning motivation and understanding of religious concepts. The Islamic story method is believed to be able to present learning materials in an interesting, contextual, and easily internalized way, so that it has the potential to increase students' emotional and cognitive involvement in the learning process. Using a qualitative approach with a case study design, this study involved 10 grade VII students, 2 Islamic Religious Education (PAI) teachers, and 1 curriculum coordinator at a junior high school in Bandung. Data were collected through in-depth interviews, participant observation, and document analysis. The results showed that the Islamic story method significantly increased students' learning motivation through the formation of empathy, character identification, and enjoyable learning experiences. In addition, this method also deepens the understanding of religious concepts by concretizing abstract values, forming structured mental schemes, and encouraging deep reflection. These findings indicate that the Islamic story method is effective in creating an inspiring, meaningful, and transformative PAI learning environment, offering a new perspective for pedagogical innovation in religious education.